2016
DOI: 10.15728/bbr.2016.13.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Victories and Defeats on the Attitude of Soccer Fans: a Study Concerning Pitchman, Involvement and Fanaticism

Abstract: This paper aims to analyze the attitude of soccer fans after the outcome of matches under the influence of a pitchman (celebrities and idols), involvement and fanaticism. The literature was supported by the concepts of happiness and attitude applied to sports, interacting with the literature on the influence of the pitchman (studies 1 and 2), involvement (study 3) and fanaticism (study 4). The data was collected in four rounds of the Brazilian soccer league, comprising 931 fans of the 16 best teams in the coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
2
0
1
Order By: Relevance
“…H1 suggested that fan satisfaction with the team positively influences the intention to purchase products in the team colors; the analysis results (= 0.33; f² = 0.06; q² = 0.03; p-value < 0.05) indicate a positive and significant effect, supporting the hypothesis. The results are in accordance with the results obtained by Fleury et al (2016), who suggested customer satisfaction has a strong and positive impact on purchase intention. Thus, the present results are in line with previous studies (Katz et al, 2020;Silva, 2020;Sullivan et al, 2021), because satisfaction tends to have a positive influence on intention and…”
Section: Discussion Of Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…H1 suggested that fan satisfaction with the team positively influences the intention to purchase products in the team colors; the analysis results (= 0.33; f² = 0.06; q² = 0.03; p-value < 0.05) indicate a positive and significant effect, supporting the hypothesis. The results are in accordance with the results obtained by Fleury et al (2016), who suggested customer satisfaction has a strong and positive impact on purchase intention. Thus, the present results are in line with previous studies (Katz et al, 2020;Silva, 2020;Sullivan et al, 2021), because satisfaction tends to have a positive influence on intention and…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…This identification implies an attitude towards the team, which, in turn, can positively influence the intention of fans to purchase products related to the favored team (Biscaia et al, 2018;Sousa & Vieira, 2018). Fleury, Nogami, Mazzon, and Veloso (2016) point out that consumption is directly related to fan satisfaction with and the situation of the team-that is, victories tend to provide an incentive for fan consumption, in the same way that defeats diminish this intention. For this purpose, satisfaction is analyzed from the point of view of the soccer team's performance related to fan intention to purchase products in the team colors; that is, it seeks to understand if, as satisfaction with the team increases, the fan intention to purchase products in the team colors increases as well.…”
Section: Fan Satisfactionmentioning
confidence: 99%
“…For instance, they may engage either their "objective rationality" or "subjective sensibility" when choosing between different types of products. Studies have shown that involvement will affect consumers' information processing, attitudes toward advertising, and decisions to purchase products (Fleury et al, 2016;Harmeling et al, 2017). We propose that when receiving advertised information about a product, a consumer with high personal involvement will invest greatly in and pay much attention to the advertised information.…”
Section: Moderating Effect Of Personal Involvementmentioning
confidence: 99%
“…O nível de envolvimento dos torcedores com seus clubes é um diferencial para ações de marketing mais eficazes ao se comparar com segmentos convencionais. Isso ocorre em razão do mercado futebolístico possuir a lealdade ao time como fator de barreira de entrada para a concorrência, uma vez que um torcedor não está disposto a consumir ofertas de outros clubes (FLEURY et al, 2016). Nesse sentido, a oportunidade para criar retorno em investimentos em ações de marketing nos clubes pode ser considerada privilegiada.…”
Section: Introductionunclassified